4CPS-002 Effectiveness and safety of monoclonal antibodies for migraine prevention after two and a half years of clinical experience. Issue 1 (23rd March 2023) - Fresan, D; Yerro, A; Pastalle, A; Garcia, C; Calvo, M; Ortega, I; Lacalle, E; Juanbeltz, R; Idoate, AI; Sarobe, MT; Noceda, MM
Abstract : Background and Importance: Erenumab, galcanezumab and fremanezumab were approved in 2019 for migraine crisis prevention. Efficacy and safety were demonstrated in three-months lasting clinical trials. At present, long-term effectiveness and safety can be analysed. Aim and Objectives: To evaluate the effectiveness and safety of monoclonal antibodies (mAb) utilised in migraine after two-and-a-half years of clinical use. Material and Methods: Prospective, observational study conducted in a tertiary hospital (December 2019 to June 2022). Data were obtained from patients' medical records (approved by our Ethics Committee). Effectiveness and tolerance are evaluated 3 months after initiation and if it is effective and well tolerated it is maintained up to 12 months. Response is defined as a decrease in headache and/or migraine days per month ≥50% compared to baseline and/or a significant improvement in quality of life (measured by HIT-6 and MIDAS scales). If partial response (PR) (decrease ≤50%) or adverse effects (AE) another mAb can be employed with different mechanism of action. If lack of response (LR) (decrease ≤25%) treatment is suspended. If response is achieved during the last months, the mAb can be maintained for another year. Results: 253 patients initiated treatment with a mAb. 69% (n:175) completed 12 months of treatment with effectiveness (responders) and 31% (n:78) stopped at third-month evaluation (PR/LR patients and AE-suffering patients), 42 of which changed to a second mAb. Ending reasons were: PR/LR (n:52), PR/LR and AE (n:9), AE (n:8) and others not related to the treatment (n:9). After completing 12 months, 140 patients stopped the treatment; 25 maintained it for another treatment course, some of which have already started a third course (median duration: 23 [17-37]), and 10 switched to a second mAb. Regarding safety, 33% (n:83) of patients reported at least one AE during the treatment with the first and/or second mAb, being the reason for discontinuation in 7% (n:17) of patients (due to vertigo and constipation, mainly). Most frequent AE were vertigo/dizziness (17%, n:45), constipation (13%, n:33) and skin rashes after injection (4%, n:11). Conclusion and Relevance: Anti-CGRP mAb are effective and safe treatments that improve migraine suffering patients' quality of life. A significant percentage of patients completes the treatment course and only 7% of patients discontinues the mAb due to intolerance. References and/or Acknowledgements: Conflict of Interest: No conflict of interest